Clove (Syzygium aromaticum) Effect on Growth Malassezia Furfur and Aspergillus sp on Media - Leka Lutpiatina1 , Pebri Fitria Lestari2 , Dwi Intan Purnama Sari2 , Haitami1 , Rifqoh1 , Nurlailah1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Malassezia furfur and Aspergillus sp are fungi associated with infection in humans. One of the plants that can use as anti fungi is clove (Syzygium aromaticum). Aim: The purpose of this study was to determine the growth barriers of Malassezia furfur and Aspergillus sp on media with the addition of Clove Powder (Syzygium aromaticum). Material and Method: The equipment used by cloves (Syzygium aromaticum) is a part of the reddish green flower. The samples used in this study were Malassezia furfur and Aspergillus sp. Specimens planted on Saboraud Dextrose Agar media with the addition of clove powder (Syzygium aromaticum) in various concentrations. Results: Malassezia furfur in media with clove powder concentration of 0%; 0.05%; 0.1% shows the number of colonies 1330; 1135; 765. Aspergillus niger, Aspergillus flavus, Aspergillus fumigatus on media with clove powder concentration of 0%; 0.05%; 0.2% indicates colony diameter of 6.8 cm; 5 cm; 3.7 cm (Aspergillus niger), 6.7 cm; 5 cm; 4.3 cm (Aspergillus flavus), 7 cm; 5 cm; 2.3 cm (Aspergillus fumigatus). Conclusion: Media with Addition of Clove Powder (Syzygium aromaticum) can inhibit the growth of Malassezia furfur and Aspergillus sp.